ANALISIS TOKOH UTAMA DALAM NOVEL SUPERNOVA EPISODE PETIR KARYA DEWI LESTARI TINJAUAN PSIKOLOGI SASTRA - Andi Srimularahmah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2020)
Abstract: Analysis of Main Character in Novel Supernova, Episodes of Lightning by Dewi Lestari, Review of Literary Psychology. This study aims to analyze the main character. This study uses a literary psychology approach. The literary psychology approach examines the things that cause the psychological conditions experienced by the main character and the factors that affect the psychological conditions experienced by the main character. The method used in this research is qualitative method. This method prioritizes process rather than results, because literary works are a phenomenon that causes many interpretations. The results showed the toughness of the main character caused by several factors. As the main character can overcome the psychological conditions experienced by the main character by managing the mind properly. The psychological condition experienced by the main character is unusual, but with the help of the people around him, the main character is able to overcome the problem. Her problem was overcome because of the help of a character named Mrs. Sati. Apart from that, the main character often interacts with other characters in the novel, namely the Dedi character, the Watti character, the Mpret character and the Kewoy character. In dealing with unusual mental conditions, the main character performs a series of exercises to relax his brain so that he can control the subconscious brain.